(untitled) (Journal of Partial Differential Equations, 2023)
In this paper, we are interested in a free boundary problem for a chemotaxis model with double free boundaries. We use contraction mapping principle and operator-theoretic approach to establish local solvability of a chemotaxis system in 1-Dimensional domain with non-constant coefficient free boundaries.